COLONIAL LEGACIES IN INDONESIA'S URBANIZATION AND URBAN HOUSING: Past, Present, and Future - Eun Young Choi (MAHABBAH: Journal of Religion and Education, 2022)
Since the 1980s, Indonesia has experienced rapid urbanization, and it has become one of the countries with the exponential growth of urban population. Densified urban population is worsening environmental issues such as particulate air pollution, water pollution, and waste disposal. Environmental injustice of poverty and the extreme polarization of rich and poor are increasing in Indonesia’s urban societies. Ecological crisis due to climate change in the Anthropocene is closely associated with the nature and culture binary that disconnects human-world relationships. As Indonesia had been colonized by the Dutch for 350 years and occupied by Imperial Japan during World War II, the built environment has become the embodiment of colonial legacies that bequeaths the dichotomy of nature and culture through urban spaces and housings. By engaging with my lived experiences in Jakarta – the capital of Indonesia – and the historical references of Indonesia’s development of the built environment and urban housing, I will discuss the nature and culture binary as the colonial legacies in Indonesia’s built environment. I argue that the formation of colonial whiteness grounded on the nature and culture binary has evolved to transmit and preserve colonial legacies by a new medium of industrial capitalism. The emergence of gate communities, luxury housings and skyscrapers, and the maintenance of room layouts from the colonial period are the specific features of the corporeal manifestations of everlasting colonialism in Indonesia’s built environment. In response to Indonesia’s urbanization in the Anthropocene, I suggest Timothy J. Gorringe’s theology of grace to call for the need for a contextualized theology of grace for Indonesia that could transform and reimagine the built environment in light of the immanence and transcendence of God.